Advances in transcorneal electrical stimulation: From the eye to the brain - Agadagba, Stephen K.; Lim, Lee Wei; Chan, Leanne Lai Hang (Frontiers in Cellular Neuroscience, 2023)
The mammalian brain is reported to contain about 106-109 neurons linked together to form complex networks. Physiologically, the neuronal networks interact in a rhythmic oscillatory pattern to coordinate the brain’s functions. Neuromodulation covers a broad range of techniques that can alter neuronal network activity through the targeted delivery of electrical or chemical stimuli. Neuromodulation can be used to potentially treat medical conditions and can serve as a research tool for studying neural functions. Typically, the main method of neuromodulation is to electrically stimulate specific structures in both the central and peripheral nervous systems via surgically implanted electrodes. Therefore, it is imperative to explore novel and safer methods for altering neuronal network activity. Transcorneal electrical stimulation (TES) has rapidly emerged as a non-invasive neuromodulatory technique that can exert beneficial effects on the brain through the eyes. There is substantial evidence to show that TES can change the brain oscillations in rodents. Moreover, the molecular data clearly shows that TES can also activate non-visual brain regions. In this review, we first summarize the use of TES in the retina and then discuss its effects in the brain through the eye-brain connection. We then comprehensively review the substantial evidence from electrophysiological, behavioral, and molecular studies on the role of TES on modulating neurons in the brain. Lastly, we discuss the implications and possible future directions of the research on TES as a non-invasive tool for neuromodulation of the brain via directly stimulating the mammalian eye.